2005
DOI: 10.2174/1389450053765888
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules with EGFR-TK Inhibitor Activity

Abstract: Specific and reversible EGFR tyrosine kinase inhibitors (TKI) such as gefitinib and erlotinib are clinically active in advanced or metastatic NSCLC and both are approved in various countries for the treatment of patients that failed prior chemotherapy. Erlotinib has also prolonged survival in pancreatic cancer patients when added to gemcitabine and regulatory approval in this disease is being sought. Additional promising activity has been seen in other tumor types, such as ovarian cancer or head and neck malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…16 Prior preclinical and clinical studies have shown decreased EGFR and diminished activation in unproven surrogates. 19,32 To our knowledge, this is one of the first studies to provide tumor-specific evidence of tyrosine kinase inhibition by gefitinib in a clinical setting. We also demonstrated that inhibition of p-EGFR results in the inhibition of downstream signaling molecules known to transmit the EGFR growth response.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…16 Prior preclinical and clinical studies have shown decreased EGFR and diminished activation in unproven surrogates. 19,32 To our knowledge, this is one of the first studies to provide tumor-specific evidence of tyrosine kinase inhibition by gefitinib in a clinical setting. We also demonstrated that inhibition of p-EGFR results in the inhibition of downstream signaling molecules known to transmit the EGFR growth response.…”
Section: Discussionmentioning
confidence: 94%
“…17 Gefitinib inhibits EGF-stimulated growth of ovarian cancer cells in vitro; this effect is cytostatic, with an increase in apoptosis observed at higher doses and when, used in combination with conventional chemotherapy, producing supraadditive growth arrest. 18,19 Gefitinib also has been tested in xenograft models of ovarian cancer, resulting in inhibitory effects on cell growth and increased survival of mice in the treatment groups. 16,20 Phase I trials of gefitinib in solid tumors, including EOC, have demonstrated tolerable toxicity and promising clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…The variety of approaches currently used to target EGFR includes small monoclonal antibody strategy to block ligand binding and TK inhibitors (5)(6)(7). Over the past 10 years, molecules that inhibit receptor autophosphorylation and downstream intracellular signaling have been developed and have shown significant antitumor activity in vitro (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…These discoveries have lead to the strategic development of novel agents targeting the EGFR for the treatment of human malignancies (4). Of these, the two most clinically advanced strategies are the monoclonal antibodies (mAb), which block the extracellular ligand-binding domain, and small molecule tyrosine kinase inhibitors (TKI), which target ATP-binding sites located in the intracellular tyrosine kinase domain of the EGFR (3,5,6). Three such agents, i.e., the anti-EGFR mAb cetuximab (Erbitux), and the TKIs, gefitinib and erlotinib, have now been approved for the treatment of patients with metastatic colorectal cancer and nonsmall cell lung cancer, respectively (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the two most clinically advanced strategies are the monoclonal antibodies (mAb), which block the extracellular ligand-binding domain, and small molecule tyrosine kinase inhibitors (TKI), which target ATP-binding sites located in the intracellular tyrosine kinase domain of the EGFR (3,5,6). Three such agents, i.e., the anti-EGFR mAb cetuximab (Erbitux), and the TKIs, gefitinib and erlotinib, have now been approved for the treatment of patients with metastatic colorectal cancer and nonsmall cell lung cancer, respectively (5,6). Despite objective responses to the EGFR inhibitors in a small fraction of patients, there has been no clear association between the levels of tumor EGFR expression and response to treatment with the EGFR inhibitors (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%